Enhancement of shelf life of paneer by surface salt treatment - Malodia, H K; Beniwal, B S (Indian Journal of Dairy Science, 2019)
Paneer was prepared and cut into cubes of three sizes i.e. 1.5, 2.5 and 3.5 cm. Their surfaces were treated with two concentrations (0.8 and 1.2 % w/w basis) of dry common salt. They were packed in LDPE (50-55 micron) packages and stored at 3 different temperatures i.e. 20Â±20C, 5Â±20C and -15Â±20C. The paneer cubes of 2.5 cm size served as control. It was revealed that the paneer cube of 1.5 cm cube size with 1.2 % salt application had the longest shelf life as evidenced by the sensory scores; supported by lower TBA, FFA and NPN values. Paneer cubes of 1.5 cm size had a score above â€œlike slightlyâ€ even on the tenth day of storage at 50C. All the samples stored at -150C were acceptable on 60th day; however, paneer cubes of 1.5 cm size and 1.2% salt scored high on the sensory scale.